Are Urban Children really healthier? - Ellen van de Poel; Owen O'Donnell; Eddy van Doorslaer (Tinbergen Institute, 2007)
On average, child health outcomes are better in urban than in rural areas of developing countries. Understanding the nature and the causes of this rural-urban disparity is essential in contemplating the health consequences of the rapid urbanization taking place throughout the developing world and in targeting resources appropriately to raise population health. We use micro data on child health taken from the most recent Demographic and Health Surveys for 47 developing countries. First, we document the magnitude of rural-urban disparities in child nutritional status and under-five mortality across all 47 developing countries. Second, we adjust these disparities for differences in population characteristics across urban and rural settings. Third, we examine rural-urban differences in the degree of socioeconomic inequality in these health outcomes. We find considerable rural-urban differences in mean child health outcomes. The rural-urban gap in stunting does not entirely mirror the gap in under-five mortality. The most striking difference between the two is in the Latin American and Caribbean region, where the gap in stunting is more than 1.5 times higher than that in mortality. On average, the rural-urban risk ratios of stunting and under-five mortality fall by respectively 53% and 59% after controlling for household wealth. Controlling thereafter for socio-demographic factors reduces the risk ratios by another 22% and 25%. In a considerable number of countries, the urban poor actually have higher rates of stunting and mortality than their rural counterparts. The findings imply that there is a need for programs that target the urban poor, and that this is becoming more necessary as the size of the urban population grows.
Keywords: I12; I31; O53; 330; child health; urban-rural inequality; nutrition; child mortality; Kinder; Gesundheit; Stadt; Ernährung; Kindersterblichkeit; Entwicklungsländer